GAMBARAN BUDAYA ENRYO DALAM FILM MARUMO NO OKITE KARYA SAKURAI TSUYOSHI DAN ASOU KUMIKO - Rika Andartik; Sri Oemiati (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2015)
Japanese people put forward a kind of politeness or indirectness, specifically referred to as enryo, in their life. Enryo is a Japanese culture that is always maintained. For Japanese, enryo controls unacceptable behaviors. Enryo can be seen in movies, dramas, or other literary works. One of the movies that show enryo is Marumo no Okite. Enryo in this movie was analyzed by using Wierzbickaâ€™s theory. The result demonstrates that enryo deals with a semantic component as indicated by the proposition of â€œI cannot say/do this: â€œI want this, I donâ€™t want thisâ€. If one says/does this, he or she will get a bad thing due to his or her words/actions. Enryo is present in Japanese life because there is a feeling of reluctance when one has to deal with other people.Keywords: enryo, shame, politeness, main character